Inorganic Triphenylphosphine. Issue 48 (8th November 2018) - Gorman, Adam D.; Bailey, Jonathan A.; Fey, Natalie; Young, Tom A.; Sparkes, Hazel A.; Pringle, Paul G.
Abstract: A completely inorganic version of one of the most famous organophosphorus compounds, triphenylphosphine, has been prepared. A comparison of the crystal structures of inorganic triphenylphosphine, PBaz3 (where Baz=B3 H2 N3 H3 ) and PPh3 shows that they have superficial similarities and furthermore, the Lewis basicities of the two compounds are remarkably similar. However, their oxygenation and hydrolysis reactions are starkly different. PBaz3 reacts quantitatively with water to give PH3 and with the oxidizing agent ONMe3 to give the triply‐O‐inserted product P(OBaz)3, an inorganic version of triphenyl phosphite; a corresponding transformation with PPh3 is inconceivable. Thermodynamically, what drives these striking differences in the chemistry of PBaz3 and PPh3 is the great strength of the B−O bond. Abstract : Inorganic versus organic : the molecular structures and Lewis basicities of triphenylphosphine and tris(2‐borazinyl)phosphine appear similar but their hydrolysis and oxygenation chemistry could hardly be more contrasting.